Enteric Coated Pellets with Lactoferrin for Oral Delivery: Improved Shelf Life of the Product - Nika Kržišnik; Blaž Grilc; Robert Roškar (Pharmaceutics)
Background/Objectives: Lactoferrin (Lf), a multifunctional iron-binding protein, has considerable potential for use as an active ingredient in food supplements due to its numerous positive effects on health. As Lf is prone to degradation, we aimed to develop a formulation that would ensure sufficient stability of Lf in the gastrointestinal tract and during product storage. Methods: A simple, efficient, and well-established technology that has potential for industrial production was used for the double-coating of neutral pellet cores with an Lf layer and a protective enteric coating. Results: The encapsulation efficiency was 85%, which is among the highest compared to other reported Lf formulations. The results of the dissolution tests performed indicated effective protection of Lf from gastric digestion. A comprehensive stability study showed that the stability was similar regardless of the neutral pellet core used, while a significant influence of temperature, moisture, product composition, and packaging on the stability of Lf were observed, and were therefore considered in the development of the final product. The experimentally determined shelf life is extended from 15 to almost 30 months if the product is stored in a refrigerator instead of at room temperature, which ensures the commercial applicability of the product. Conclusion: We successfully transferred a technology commonly used for small molecules to a protein-containing product, effectively protected it from the destructive effects of gastric juice, and achieved an acceptable shelf life.